PENINGKATAN PENGETAHUAN KONSEP BILANGANMELALUI OBJEK LINGKUNGAN BELAJAR PADA ANAK - Elina, Seselia; Fadillah, Fadillah; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated Â cognitive of children in recognizing the concept of numbers.1) The child has not been able to call and show the symbol of the number 1-10, 2) The child has not been able to make a sequence of numbers 1-10 according to the object, 3) The child has not been able to connect the number with how to draw the line according to the number of objects. problem this study "Is through media learning environment can increase the knowledge of the concept of numbers in children aged 5-6 years in kindergarten TK good Pontianak?". The objective of the research is to increase the knowledge of the concept of numbers through object-based media learning environment in children aged 5-6 years. This form of research is a classroom action research. The subjects of the study were teachers 1 person and children amounting to 28 people. The results of research conducted: 1) Planning learning by using media learning environment to increast knowledge of the concept of numbers categorized "good". 2) Implementation of learning by using object mediaenvironment. 3) Increasing knowledge of the concept of numbers in Good Shepherd Kindergarten Pontianak.Â Keywords: Concept Numbers, Object-Based Media Learning Environment.